2021
DOI: 10.3390/molecules26144135
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Polymer Nanocomposites for Mechanical Properties

Abstract: Epoxy resins, due to their high stiffness, ease of processing, good heat, and chemical resistance obtained from cross-linked structures, have found applications in electronics, adhesives coatings, industrial tooling, and aeronautic and automotive industries. These resins are inherently brittle, which has limited their further application. The emphasis of this study is to improve the properties of the epoxy resin with a low-concentration (up to 0.4% by weight) addition of Multi-Walled Carbon Nanotubes (MWCNTs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Additionally, KSiO 2 has less viscosity than Na 2 SiO 3 [47]. Potassium alkali agent decreased viscosity results in greater strength and durability with less shrinkage and porosity [50,51]. When compared the curing condition of GPC with ambient and oven-cured conditions, it was concluded that the oven curing condition shows a higher CS value than the ambient condition [48].…”
Section: Effect Of the Activator And A/b On Csmentioning
confidence: 98%
“…Additionally, KSiO 2 has less viscosity than Na 2 SiO 3 [47]. Potassium alkali agent decreased viscosity results in greater strength and durability with less shrinkage and porosity [50,51]. When compared the curing condition of GPC with ambient and oven-cured conditions, it was concluded that the oven curing condition shows a higher CS value than the ambient condition [48].…”
Section: Effect Of the Activator And A/b On Csmentioning
confidence: 98%
“…A measured amount of epoxy is taken and preheated to reduce its viscosity before ultrasonication. [18,19] Filler materials were added to ethanol solvent and sonicated for 10 min. The filler materials were then added to epoxy and initially mixed manually for about 5 min, which was then followed by sonication for about 50 min.…”
Section: Preparation Of Nanocompositesmentioning
confidence: 99%
“…With an optimum value of 45.75 with standard deviation of 6.11092, R-squared, training value was obtained as 70.25% and root mean squared error (RMSE) as 3.2390. The mean absolute percentage of error (MAPE) was 0.1247 [ 57 , 58 , 59 , 60 ].…”
Section: Statistical Analysis Of Testsmentioning
confidence: 99%